Sérieuse, audacieuse, bienheureuse... Généreuses! Rencontre avec Isabelle Panneton, Marie Pelletier et Ana Sokolovic - Davoine, Françoise (Circuit : musiques contemporaines, 1999)
In this exchange with three women composers, Françoise Davoine draws a portrait of their risks, anguish and preoccupations. The speaking-style of the text has been preserved here, giving freshness to the statements as each woman talks about her situation, and the creative process, etc.
Publisher: Les Presses de l'Université de Montréal

Céline Dion et l'identité québécoise. « La petite fille de Charlemagne parmi les grands ! » - Demers, Frederic (VLB Éditeur, 1999)
Pourquoi Céline Dion est-elle une figure identitaire de premier plan aux yeux de la plupart des Québécois? Serait-ce parce qu'elle incarne l'équilibre qu'il recherchent désormais entre la préservation d'un héritage culturel particulier et l'ouverture à l'Autre sous le poids de la mondialisation et du métissage?

Pauline Julien. La vie à mort - Desjardins, Louise (Leméac, 1999)
La vie et la carrière de Pauline Julien sont un véritable roman. Née à Trois-Rivières en 1928, elle commence son parcours de comédienne à Québec et à Montréal avant de tenter sa chance à Paris où elle débute comme diseuse et chanteuse dans les boîtes à chansons de la rive gauche. Interprète de Bertolt Brecht, Boris Vian, Léo Ferré, elle côtoie Barbara, Ricet Barrier et Anne Sylvestre. Elle ajoute à son répertoire, au fil d'une carrière entre le Québec, la France, la Suisse et la Belgique, les chansons de Raymond Lévesque, Gilles Vigneault, Michel Tremblay, Réjean Ducharme, Félix Leclerc... Après son arrestation en octobre 1970, cette militante passionnée devient la figure de proue d'une nouvelle affirmation culturelle, politique et féminine du Québec. Sa vie publique d'interprète cachait une femme angoissée, passionnée d'écriture. Pauline Julien a légué ses carnets personnels, tenus pendant près de quarante ans, à Louise Desjardins qui les a utilisés pour écrire le parcours d'une femme marquante du Québec moderne, des plus attachantes aussi, une femme de cœur et de tête, une femme de parole à fleur de peau, libre, qui avait l'âme à la tendresse... Pauline Julien a mené sa vie tambour battant, emportée par son tempérament fougueux et sa voix si particulière, qui fait vibrer le cœur de toutes les générations.

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

Ana Sokolovic : entrevue avec Jean Lesage - Lesage, Jean (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

À propos de cinq œuvres symphoniques de Linda Bouchard - Nattiez, Jean-Jacques (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Isabelle Panneton : à contretemps - Panneton, Isabelle (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Estelle Lemire : portrait de l'artiste-compositeure - Provost, Serge (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Maureen Forrester: Canada's Charming Contralto :a Biography for Young People - Roy, Lynette (Orchid Communications, 1999)

Linda Bouchard : la musique de Linda Bouchard - Tourigny, Maurice (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Dr. Violet Balestreri Archer, Her Life, Her Vocal Literature, and Her Influence on Contemporary Canadian Music - Valente, Liana Elsie (Université de Caroline du Sud, 1999)
Keywords: Pas de lien web

Nanette - Workman, Nanette (Éditions Stanké, 1999)
La vie et la carrière de la chanteuse à travers des photos personnelles et d'archives, de sa naissance à 1995.

Céline Dion, the ADISQ Controversy, and the Anglophone Press in Canada - Young, David (Canadian Journal of Communication, 1999)
Abstract: ADISQ, the organization that honours excellence in the Quebec music industry, gave francophone singer Céline Dion an award for being the Anglophone Artist of the Year in 1990. At the ADISQ gala that year, which was televised live across Canada, Dion refused to accept the award. Dion's decision to not accept the award, and the statement she made when turning it down, became the basis for a controversy that received a great deal of coverage in Canada's anglophone press. This paper examines anglophone press coverage of the ADISQ controversy involving Dion. After outlining press coverage of Dion and ADISQ during the years prior to the controversy, the paper identifies how the controversy began and analyses the issues that dominated the coverage. The paper also examines follow-up coverage of the controversy; it identifies how subsequent news stories on Dion, including some that were written several years later, linked the controversy to other issues. Résumé: L'ADISQ, l'organisme qui reconnaît l'excellence dans l'industrie de la musique au Québec, accorda à la chanteuse francophone Céline Dion le prix du Meilleur Artiste anglophone de l'année 1990. Au gala de l'ADISQ cette année-là-qui fut télévisé en direct partout au Canada-Dion a refusé d'accepter le prix. Cette décision, ainsi que les commentaires que Dion a faites en refusant le prix, suscitèrent une controverse qui fit couler beaucoup d'encre dans la presse anglophone au Canada. Cet article examine comment la presse anglophone a couvert cette controverse de l'ADISQ impliquant Dion. Après avoir tracé les grandes lignes des reportages sur Dion et l'ADISQ dans les années précédant la controverse, cet article identifie comment la controverse commença et analyse les questions qui dominèrent dans la couverture de celle-ci. Cet article examine en outre la couverture suivant la controverse; il identifie comment des reportages ultérieurs sur Dion, y compris certains qui apparurent plusieurs années plus tard, associèrent la controverse à d'autres sujets.
Number: 4
Keywords: ADISQ; Anglophone press; Céline Dion; Journalism